Intranasal Insulin Attenuates the Long-Term Adverse Effects of Neonatal Hyperglycemia on the Hippocampus in Rats - McClure Yauch, Lauren; Ennis-Czerniak, Kathleen; Frey Ii, William H; Tkac, Ivan; Rao, Raghavendra B (Developmental neuroscience, 2022)
Hyperglycemia due to relative hypoinsulinism is common in extremely preterm infants and is associated with hippocampus-mediated long-term cognitive impairment. In neonatal rats, hypoinsulinemic hyperglycemia leads to oxidative stress, altered neurochemistry, microgliosis, and abnormal synaptogenesis in the hippocampus. Intranasal insulin (INS) bypasses the blood-brain barrier, targets the brain, and improves synaptogenesis in rodent models, and memory in adult humans with Alzheimer's disease or type 2 diabetes, without altering the blood levels of insulin or glucose. To test whether INS improves hippocampal development in neonatal hyperglycemia, rat pups were subjected to hypoinsulinemic hyperglycemia by injecting streptozotocin (STZ) at a dose of 80 mg/kg i.p. on postnatal day (P) 2 and randomized to INS, 0.3U twice daily from P3-P6 (STZ + INS group), or no treatment (STZ group). The acute effects on hippocampal neurochemical profile and transcript mRNA expression of insulin receptor (Insr), glucose transporters (Glut1, Glut4, and Glut8), and poly(ADP-ribose) polymerase-1 (Parp1, a marker of oxidative stress) were determined on P7 using in vivo 1H MR spectroscopy (MRS) and qPCR. The long-term effects on the neurochemical profile, microgliosis, and synaptogenesis were determined at adulthood using 1H MRS and histochemical analysis. Relative to the control (CONT) group, mean blood glucose concentration was higher from P3 to P6 in the STZ and STZ + INS groups. On P7, MRS showed 10% higher taurine concentration in both STZ groups. qPCR showed 3-folds higher Insr and 5-folds higher Glut8 expression in the two STZ groups. Parp1 expression was 18% higher in the STZ group and normal in the STZ + INS group. At adulthood, blood glucose concentration in the fed state was higher in the STZ and STZ + INS groups. MRS showed 59% higher brain glucose concentration and histochemistry showed microgliosis in the hippocampal subareas in the STZ group. Brain glucose was normal in the STZ + INS group. Compared with the STZ group, phosphocreatine and phosphocreatine/creatine ratio were higher, and microglia in the hippocampal subareas fewer in the STZ + INS group (p < 0.05 for all). Neonatal hyperglycemia was associated with abnormal glucose metabolism and microgliosis in the adult hippocampus. INS administration during hyperglycemia attenuated these adverse effects and improved energy metabolism in the hippocampus.